+0  
 
0
38
3
avatar

i need to ask so im trying to do this calculation and it gives me two answers why and how?

 Feb 4, 2019
 #1
avatar+79 
0

What's the calculation?

 Feb 5, 2019
 #2
avatar
0

(3x+3)(x-4)=3(x+1)

 Feb 5, 2019
 #3
avatar+99309 
+1

\((3x+3)(x-4)=3(x+1)\\ 3x^2-12x+3x-12=3x+3\\ 3x^2-9x-12=3x+3\\ 3x^2-9x-12-3x-3=3x+3-3x-3\\ 3x^2-12x-15=0\\ \text{divide both sides by 3}\\ x^2-4x-5=0\\ (x-5)(x+1)=0\)

 

now if 2 things multiply together to give 0 then one of them, or both of them, must equal 0.

 

so

x-5=0      or      x+1=0

x=5         or         x=-1

 Feb 5, 2019

14 Online Users

avatar
avatar
avatar